Using cortical organoids to understand the pathogenesis of malformations of cortical development - Winden, Kellen D.; Gisser, Isabel; Sahin, Mustafa (Frontiers in Neuroscience, 2025)
Malformations of cortical development encompass a broad range of disorders associated with abnormalities in corticogenesis. Widespread abnormalities in neuronal formation or migration can lead to small head size or microcephaly with disorganized placement of cell types. Specific, localized malformations are termed focal cortical dysplasias (FCD). Neurodevelopmental disorders are common in all types of malformations of cortical development with the most prominent being refractory epilepsy, behavioral disorders such as autism spectrum disorder (ASD), and learning disorders. Several genetic pathways have been associated with these disorders from control of cell cycle and cytoskeletal dynamics in global malformations to variants in growth factor signaling pathways, especially those interacting with the mechanistic target of rapamycin (mTOR), in FCDs. Despite advances in understanding these disorders, the underlying developmental pathways that lead to lesion formation and mechanisms through which defects in cortical development cause specific neurological symptoms often remains unclear. One limitation is the difficulty in modeling these disorders, as animal models frequently do not faithfully mirror the human phenotype. To circumvent this obstacle, many investigators have turned to three-dimensional human stem cell models of the brain, known as organoids, because they recapitulate early neurodevelopmental processes. High throughput analysis of these organoids presents a promising opportunity to model pathophysiological processes across the breadth of malformations of cortical development. In this review, we highlight advances in understanding the pathophysiology of brain malformations using organoid models.